2018
DOI: 10.1002/jcp.27630
|View full text |Cite
|
Sign up to set email alerts
|

Human breast cancer decellularized scaffolds promote epithelial‐to‐mesenchymal transitions and stemness of breast cancer cells in vitro

Abstract: Breast cancer, with unsatisfactory survival rates, is the leading cause of cancer‐related death in women worldwide. Recent advances in the genetic basis of breast cancer have benefitted the development of gene‐based medicines and therapies. Tissue engineering technologies, including tissue decellularizations and reconstructions, are potential therapeutic alternatives for cancer research and tissue regeneration. In our study, human breast cancer biopsies were decellularized by a detergent technique, with sodium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(48 citation statements)
references
References 50 publications
2
43
0
3
Order By: Relevance
“… 99 The authors used decellularised mammary or muscle tissues isolated from nonobese diabetic (NOD)/severe combined immunodeficient (SCID) female mice (8–12 weeks old) that supported cancer cell line survival, proliferation, migration, and invasion in culture and vascularised tumour formation after implantation into the mammary fat pads of the 8-week-old female NOD/SCID mice 99 ( Figure 5 ). Another example is the work by Liu et al 100 where decellularised human breast cancer biopsies were seeded with MCF-7 breast cancer cell line showing increased cell migration, proliferation and epithelial-to-mesenchymal transition. When treated with 5-fluorouracil, an antineoplastic agent to treat multiple solid tumours including breast, expression of stem cell markers was maintained in the recellularised scaffold with decreased apoptosis rates compared to monolayer cells.…”
Section: Use Of Decellularised Scaffolds As 3d Ex Vivo Platformsmentioning
confidence: 99%
See 1 more Smart Citation
“… 99 The authors used decellularised mammary or muscle tissues isolated from nonobese diabetic (NOD)/severe combined immunodeficient (SCID) female mice (8–12 weeks old) that supported cancer cell line survival, proliferation, migration, and invasion in culture and vascularised tumour formation after implantation into the mammary fat pads of the 8-week-old female NOD/SCID mice 99 ( Figure 5 ). Another example is the work by Liu et al 100 where decellularised human breast cancer biopsies were seeded with MCF-7 breast cancer cell line showing increased cell migration, proliferation and epithelial-to-mesenchymal transition. When treated with 5-fluorouracil, an antineoplastic agent to treat multiple solid tumours including breast, expression of stem cell markers was maintained in the recellularised scaffold with decreased apoptosis rates compared to monolayer cells.…”
Section: Use Of Decellularised Scaffolds As 3d Ex Vivo Platformsmentioning
confidence: 99%
“…The authors concluded that the decellularised breast scaffold model would help to simulate the pathogenesis of breast cancer in vitro. 100 A last example reported by Mollica et al 101 described a novel mammary-specific culture combining a self-gelling hydrogel solely composed of decellularised rat or human breast tissue ECM with a 3D bioprinting platform. The authors were able to show that large organoids/tumoroids could be established in the mammary-derived hydrogel.…”
Section: Use Of Decellularised Scaffolds As 3d Ex Vivo Platformsmentioning
confidence: 99%
“…Thus, it is expected that the dECM that is derived from cancerous tissues is more suitable for examining the role of cancerous ECM in the regulation of cancer cell behavior at primary sites. Liu et al prepared dECM from human breast cancer tissues that were cultured with the breast cancer MCF-7 cell line [62]. In the dECM, CDH1 expression decreased during culture, while the expression of the EMT genes VIM , ZEB1 , and SNAI1 increased.…”
Section: Examples Of Decm Utilized For Cancer Researchmentioning
confidence: 99%
“…105 In terms of examples of this approach that are specific to tissue-engineered tumor models, Lü et al used decellularized tumor ECM as a 3D scaffold for tumor engineering 106 and Liu et al decellularized human breast cancer biopsies as a breast scaffold model followed by treatment with sodium lauryl ether sulfate to simulate the pathogenesis of breast cancer in vitro. 107…”
Section: Tissue Engineering Models For the Study Of Breast Cancermentioning
confidence: 99%